2016
DOI: 10.1007/s00423-016-1403-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neuropsychological outcome and “quality of life” after glioma surgery

Abstract: Our study suggests that extended tumour resection is not necessarily linked to a loss in QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…3 Main complaint (include multiple responses) of patients with RCS < 40. They could be divided into three categories, function related issues which was the highest percentage (41%), work related issues, and disease or treatment related issues synonymous [28][29][30], while others have suggested that functional factors and QOL are not related or that functional factors alone cannot fully explain the outcome [31,32]. Accordingly, KPS = 100 signified significantly higher QOL than KPS ≤ 90 in our patient group (Online Resource 5).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…3 Main complaint (include multiple responses) of patients with RCS < 40. They could be divided into three categories, function related issues which was the highest percentage (41%), work related issues, and disease or treatment related issues synonymous [28][29][30], while others have suggested that functional factors and QOL are not related or that functional factors alone cannot fully explain the outcome [31,32]. Accordingly, KPS = 100 signified significantly higher QOL than KPS ≤ 90 in our patient group (Online Resource 5).…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, the term functional outcome was sometimes used as synonymous with QOL [28][29][30]. However, functional outcomes such as Karnofsky Performance Status (KPS) and neuropsychological function do not necessarily conform with QOL in clinical practice [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…However, the present study identified improvements in all neurocognitive domains at long-term follow-up, both compared to preoperative baseline as well as the short-term postoperative phase. Of particular note, we conducted long-term follow-up examinations after a median period of 18.3 months, whereas previous studies evaluating neurocognitive changes over the postoperative period reported on long-term neurocognitive assessments 3 to 6 months after surgery ( 32 , 39 42 ). By contrast, we defined neurocognitive assessments within the first 9 postoperative months to fall into short-term evaluations (with the median coming up to 4.1 months), since we observed a significant change in patients´ neurocognitive performances at this time point during their course of disease.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of the observed cognitive alterations is difficult to answer because cognition does not correlate with quality of life (Boele et al, ; Wolf et al, ). Nevertheless, our findings can have clinical implications.…”
Section: Discussionmentioning
confidence: 99%